Investigation on Depression of College Students Majoring in Physical Education and Nonphysical Education: A StudyBased on the Age Region and Gender of 374 Students. (2nd September 2022) - Ding, Xiaofen; Tang, Nian
Abstract : In the research on the relationship between depression and college students' major, there are some differences in the degree of depression between sports major and nonsports major students. Based on these results, we assume that there is the possibility of emotional differences between professional and nonprofessional sports. A total of 374 samples of students majoring in physical education and nonphysical education at the same university were analyzed by using the methods of literature review and data analysis. A total of 188 subjects, including 121 males and 253 females (186 majoring in sports and nonsports), were asked to fill in the SDS (Self-Rating Depression Scale). SDS is widely used in rough screening, emotional state evaluation, investigation, and scientific research of outpatients in clinical psychology departments. The research obtained the difference in depression degree in the whole sample and further compared the depression degree of students of different ages and native places. Statistical analysis was performed on all data using SPSS 23.0 software. Basic data description, paired chi-square analysis, and covariance analysis were used. The results show that in this sample, the maximum value (minimum/maximum value) of one item of the total depression score of nonphysical education students exceeds the average value by 3 standard deviations, and this shows that the general level of depression scores of non-PE majors is high; most non-PE majors are in mild depression, which is equal to the number of PE majors who are in a normal mood; and nonsports majors in cities are more likely to have mild depression.